Arbitration of labour disputes in Mauritius - Hossen, Rashid (Obiter, 2020)
The evolution of labour law on Mauritius started with the repeal of the “code noir” (literally the black code) which was introduced in France in 1685 and extended to the island in 1723. It contained inhumane provisions that treated a slave as merchandise, as the property of his master which was subject to a list of punishments for not obeying the orders of the latter. Freedom of movement was then a crime.